تأثير حجم البذور على بعض المؤشرات الكميّة لنمو وتطوّر بادرات الخرنوب Ceratonia siliqua L. (Latakia University Journal -Biological Sciences Series, 2016)
هدفت هذه الدراسة الحصول على شتول متوازنة و متفوقة في نموها, من خلال البحث في تأثير حجم البذور على نموّ و تطور بادرات الخرنوب Ceratonia siliqua L. النامية في أوعية الميني ريزوترونات في غرفة النمو بمركز بحوث اللاذقية. قسمت البذور إلى ثلاث فئات (كبيرة الحجم LS , الشاهد CS , صغيرة الحجم SS) ودرست عدة مؤشرات كميّة خاصة بنمو وتطور المجموع الخضري والجذري للبادرات ولمدة ثلاثة أشهر . بالنسبة للجهاز الجذري, أشارت النتائج إلى تفوق معنوي عالٍ في قيم البذور الكبيرة الخاصة بمعدل نمو الجذر الرئيسي كالطول الكلي (سم) وسرعة النمو (سم/ 3 أيام) و للجذور الثانوية ( العدد الكلي, الطول الكلي/سم) على بذور الشاهد والبذور الصغيرة. وتفوق معنوي لقيم بذور الشاهد على البذور الصغيرة. كما أعطت البذور الكبيرة أعلى القيم بخصوص كافة المؤشرات المتعلقة بالمجموع الخضري كمتوسط القطر ومتوسط الطول ومتوسط عدد سلاميات الساق والأوراق, وانتهاءاً بالوزن الجاف للمجموع الخضري. دلت النتائج المتعلقة بدراسة منحنيات النمو الدوري للجذر الرئيسي والساق الرئيسية لبادرات المعاملات الثلاث على وجود تشابه كبير في المظهر العام لهذه المنحنيات مما يشير إلى عدم تأثر هذا المظهر بتغير كمية المدخرات الغذائية في البذور. ومن جهة أخرى تمّ ملاحظة ظاهرة التضاد في النمو Antagonism بين المجموعين الخضري والجذري, فمع أيّ نهاية عظمى لنمو الجذر الرئيسي يرافقها نهاية صغرى في نموّ الساق الرئيسة والعكس بالعكس .This study aimed to obtain seedlings balanced and superior in growth, by searching the effect of seed size on the growth and development of seedlings of carob tree ( Ceratonia siliqua L.) developing in containers Minirhizotron in the growth room in Research Center in Bouka-Lattakia. Seeds were divided into three categories (large-size LS, control CS, small-sized SS) and studied several quantities indicators of growth and development of the total shoot and root of the seedlings for a period of three months.For a radical system, results indicated a high significant superiority in the large seeds values for the main root of the overall growth rate such as length (cm) and the speed of growth (cm/3days) and secondary roots (total number, total length/cm) height to control and small seeds. And the significant superiority of the seeds of the control on the small seeds.It has also given large seeds higher values regarding all indicators related to the shoot system such as average diameter and average height and average number of phalanges stem and leaves, and ending with the dry weight of shoots. Results for the study of periodic growth curves for the main root and main stem of the three treatments indicated the presence of a great similarity in the overall appearance of these curves, which refers that the appearance is not affected by this change in the amount of seed size. On the other hand, the phenomenon was observed in contrast growth Antagonism clearly between the totals shoot and root with any end to the growth of main root accompanied by a junior at the end of the main stem growth and vice versa.